Neuromorphic Computing Using NAND Flash Memory Architecture With Pulse Width Modulation Scheme - Lee, Sung-Tae; Lee, Jong-Ho (Frontiers in Neuroscience, 2020)
A novel operation scheme is proposed for high-density and highly robust neuromorphic computing based on NAND flash memory architecture. Analogue input is represented with time-encoded input pulse by pulse width modulation (PWM) circuit and 4-bit synaptic weight is represented with adjustable conductance of NAND cells. PWM scheme for analogue input value and proposed operation scheme are fully compatible with existing NAND flash memory architecture to implement neuromorphic system without additional change of memory architecture. Saturated current-voltage characteristic of NAND cells eliminates the effect of serial resistance of pass cells in a synaptic string and IR drop of metal wire resistance. Multiply-accumulate (MAC) operation of 4-bit weight and width-modulated input can be accomplished in a single input pulse eliminating the additional logic operation. In addition, effect of quantization training on the inference accuracy is investigated compared to post-training quantization with 4-bit weight. Finally, the low-variance conductance distribution of NAND cells obtained by read-verify-write (RVW) scheme achieves satisfying accuracy of 98.14% and 89.6% for the MNIST and CIFAR10 datasets, respectively.